Hyperandrogenism caused by ovarian Leydig cell tumour: finding the needle in a haystack. Issue 12 (13th December 2020) - Tong, Chin Voon; Tai, Yong Ting
Abstract : Leydig cell tumours (LCTs) of the ovary are rare ovarian tumours that usually present with hyperandrogenism. Conventional radiological imagings are helpful in localising these tumours. However, some tumours may be too small to be localised before curative surgical removal. It is important to identify these androgen-secreting neoplasms which originate mostly from adrenals or ovaries because they are potentially malignant and require specific treatment. When conventional imagings are unrevealing, selective ovarian and adrenal venous sampling (SOAVS) is the next option. We report a case of LCT that was localised by SOAVS after results from other imaging modalities remained inconclusive.